PENYELENGGARAAN INOVASI DALAM PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP DI KECAMATAN TUALANG KABUPATEN SIAK - Satria, Moh Zulfie; Monalisa, Monalisa; Juliana, Septa (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2021)
The purpose of this research is to find out innovations and barriers to innovation in waste management by the Environmental Service in Tualang District, Siak Regency. This type of research is quantitative with a descriptive approach. The research population is the employees of the Environmental Service of Siak Regency and the Community of Tualang District. Sampling was done by using purposive sampling technique, so that the sample of this study was set at 51 people. Data were collected by means of observation, distributing questionnaires, and documentation. All data that has been obtained in the study are grouped and processed quantitatively. The data are presented and explained and analyzed descriptively in order to obtain research results, then conclusions can be drawn. Overall, innovation in waste management by the Environmental Service in Tualang District, Siak Regency is in the fairly implemented category. The Environmental Service in Tualang District, Siak Regency has made innovations that have been running for more than 2 years, there is a novelty and uniqueness in waste management by cooperating with the community, involving the role of the community and stakeholders, and activities financed by the Regional Budget of Siak Regency, then having an impact or benefits for the region and society. Thus, waste management innovation is in the category of quite implemented. There are several obstacles to waste management innovation in Tualang District, namely the level of population distribution, participation, guidance, counseling, and infrastructure.